2023
DOI: 10.2147/ndt.s390482
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Trends for the Same Patients with Schizophrenia Over 20 Years

Abstract: Background: Recent pharmacoepidemiology data show an increase in the proportion of patients receiving second-generation antipsychotic (SGA) monotherapy, but no studies have analyzed the same patients over a long period of time. Therefore, in this study, we retrospectively evaluated schizophrenia patients with available data for 20 years to determine whether the drug treatments in the same patients have changed in the past 20 years. Methods: The study began in April 2021 and was conducted in 15 psychiatric hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“… 3 The biperiden equivalent of total anticholinergic drug in 2021 was smaller than that in 2001, as we previously reported. 11 There was no significance between the initiation of laxative use and the daily dose of anticholinergic drugs in 2021 or 2001. This is not consistent with a previous study by Lin and their colleagues who reported that a higher dose of anticholinergic drugs was associated with increasing laxative use.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 3 The biperiden equivalent of total anticholinergic drug in 2021 was smaller than that in 2001, as we previously reported. 11 There was no significance between the initiation of laxative use and the daily dose of anticholinergic drugs in 2021 or 2001. This is not consistent with a previous study by Lin and their colleagues who reported that a higher dose of anticholinergic drugs was associated with increasing laxative use.…”
Section: Discussionmentioning
confidence: 95%
“…Previously in this survey, we reported a slow but steady substitution of SGAs for FGAs over time. 11 Since many guidelines recommend that monotherapy with SGAs is the first‐line treatment for schizophrenia, 22 , 23 , 24 polytherapy with benzodiazepine and mood stabilizers, including lithium and carbamazepine, should be minimized. In Japan, the Effectiveness of Guidelines for Dissemination and Education (EGUIDE) psychiatric treatment project, which aims to disseminate the guidelines that present the treatments for schizophrenia and major depressive disorder via education programs for psychiatrists, was reported to be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotic medications (AP) are an effective maintenance treatment for schizophrenia [1][2][3][4] and clearly reduce the risk of relapse and hospitalization. [5][6][7][8][9][10] The lack of adherence is associated with relapse and (re)admission, [10][11][12][13] and risk of suicide. [14][15][16] It has been suggested that second-generation antipsychotics (SGAs) are more effective than first-generation antipsychotics and are also better tolerated and safer, [3][4][5][6][7] which is why their use is already widespread.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] It has been suggested that second-generation antipsychotics (SGAs) are more effective than first-generation antipsychotics and are also better tolerated and safer, [3][4][5][6][7] which is why their use is already widespread. 1,3,6,8,12,[17][18][19] However, there is still debate about the use of oral or injectable long-acting (LAI) SGAs to improve adherence and treatment outcomes. [18][19][20][21][22][23][24] LAI antipsychotics have shown to improve compliance [10][11][12][13] and to reduce relapses and hospital admissions [25][26][27][28][29][30][31][32] better than oral formulations, [18][19][20][21][22][23][24][25][26][27] thus being recommended in recent years, especially in patients with poor adherence, with multiple relapses and hospitalizations, or with greater severity.…”
Section: Introductionmentioning
confidence: 99%